ELUCIDATION THE TOXICITY MECHANISM OF ZINC OXIDE NANOPARTICLE USING MOLECULAR DOCKING APPROACH WITH PROTEINS - Singh, Krishna Pal; Dhasmana, Anupam; Rahman, Qamar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: At present, toxicological tests are resource-intensive, time-consuming and require a large pool of animal models for toxicity assessment. To speed up the toxicity evaluation and to reduce animal suffering during toxicity assessment, the use of alternative methods including computational models is in high demand. The computational toxicity prediction methods are very helpful for the regulatory bodies to quickly assess the health impact of nanomaterial materials. In the present work, we have examined the mechanism of zinc oxide nanoparticle (ZnO-NP)-proteins interaction and their effect of surface chemistries of ZnO-NP on the bioactive conformation of chemokines and other cytological proteins using in silico molecular docking approaches. Methods: Molecular docking study was conducted using AutoDock 4.0 version and the visualization result using Discover Studio 4.0. Results: In the present study, we observed that ZnO-NP has high binding affinity with the mitogen-activated protein kinases (P-38), nuclear factor kappa-light-chain-enhancer of activated B cell (NF-kB) proteins, and matrix metallopeptidase-9 with docking energies âˆ’8.81, âˆ’7.64, and âˆ’7.27 Kcal/ Mol, respectively, involving with hydrogen, metal acceptor, and electrostatic interaction. The top interacting amino acid residues with ZnO-NP are GLY, PHE, ARG, ASP, GLN, and ASN. Conclusion: Thus, based on the molecular docking studies, we determine that the ZnO-NP is strongly interacting with the chemokines and other cytological proteins thus responsible for blocking of the activation stimuli for these proteins to initiate the biological signals for the proper functioning. The important interaction pattern ZnO-NP with the surface-enriched amino acid residues of chemokines and cytological proteins using molecular docking approach.